Up-regulation of genes involved in the Insulin signaling pathway (IGF1, PTEN and IGFBP1) in the endometrium may link Polycystic Ovarian Syndrome and endometrial cancer - Shafiee, Mohamad Nasir; Seedhouse, Claire; Mongan, Nigel; Chapman, Caroline; Deen, Suha; Abu, Jafaru; Atiomo, William (Elsevier, 2016)
BACKGROUND